2006
DOI: 10.1007/s11262-005-0073-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced immunogenicity to food-and-mouth disease virus in mice vaccination with alphaviral replicon-based DNA vaccine expressing the capsid precursor polypeptide (P1)

Abstract: Recently, alphavirus replicon-based DNA vaccines, also known as suicidal DNA vaccines, have emerged as an important strategy to enhance the potency of DNA vaccines. In this study, two different types of DNA vaccines encoding the capsid precursor polypeptide (P1) of foot-and-mouth disease virus (FMDV) were constructed and the immunogenicity were investigated and compared in mouse model. The first DNA vaccine, pcDP1, is a conventional plasmid DNA vaccine in which P1 was driven directly by a cytomegalovirus promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…However, we found that a DNA vaccine encoding the FMDV P1 protein could induce not only humoral responses but also cell-mediated responses (Yu et al, 2006). At the same time, we demonstrated that vaccination with the DNA vaccine encoding P1 resulted in the clearance of FMDV from the sera of immunized mice challenged by FMDV, while the DNA vaccine encoding the FMDV VP1 protein did not protect animals against the challenge (Yu et al, 2006;Shieh et al, 2001).…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…However, we found that a DNA vaccine encoding the FMDV P1 protein could induce not only humoral responses but also cell-mediated responses (Yu et al, 2006). At the same time, we demonstrated that vaccination with the DNA vaccine encoding P1 resulted in the clearance of FMDV from the sera of immunized mice challenged by FMDV, while the DNA vaccine encoding the FMDV VP1 protein did not protect animals against the challenge (Yu et al, 2006;Shieh et al, 2001).…”
Section: Discussionmentioning
confidence: 82%
“…DNA transfection and gene expression were performed according to Yu et al (2006). At 48 hrs after transfection, the plates were fixed with 3.7% formaldehyde in PBS (pH 7.4) and incubated with rabbit polyclonal anti-P1 antiserum.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations